Self -Assembled Monolayers with Peptide Nucleic Acid (PNA) Probe to Develop Electrochemical Biosensors - Zehra Banu Bahsi Oral (Düzce Üniversitesi Bilim ve Teknoloji Dergisi)
Alkanethiolself-assembled monolayers (SAMs) with Peptide Nucleic Acid (PNA) were proposedas a novel probe design in electrochemical biosensors. This paper investigatesthe optimization of PNA probe by using two different concentrations of SAMs,immobilization temperature, and two-stage immobilization process. Alkanethiolself-assembled monolayers with PNA probe immobilization and cDNA (complementaryDNA) hybridization were measured via AC voltammetry method. The small negativeshift in formal potential (-17 mV) was occurred after cDNA hybridization athigh ionic strength concentration.